An Analysis of the Economic Performance of Nepal’s Provinces - Bhattarai, Kumar (Journal of Innovation in Academia, 2024)
This study analyzes the economic performance of Nepal’s provinces by employing descriptive approach. Secondary data related to the key indicators showing economic performance of provinces, i.e. economic growth, per capita income, contribution to gross domestic product, expenditure and receipt were examined for the period 2018/19-2022/23. The findings reveal a concerning trend of weak economic growth across Nepal’s provinces. The per capita income of most of the provinces is low while provincial transfer dependency is high. Provinces were found to allocate relatively higher proportion of their budget to capital expenditure compared to re-current expenditure. Among the provinces, Bagmati, Gandaki and Koshi have relatively better economic performance compared to other provinces in terms of indicators considered.